Playing seriously: how gamification and social cues influence bank customers to use gamified e-business applications - Rodrigues, L. F.; Oliveira, A.; Costa, C. J. (Computers in Human Behavior, 2016)
The development of business applications with game features has given rise to a new trend called gamification and challenged e-banking to introduce new game elements, such as mechanics and social cues, to its traditional applications. Yet, there has been a lack of empirical evidence regarding the intention to use, these type of applications and their possible impacts on business. Here, we explore the role of gamification, socialness, and other four well-known variables (ease-of-use, usefulness, enjoyment, and intention to use) in a gamified business application and corresponding business. We proposed and evaluated a model based on the Technology Acceptance Model to better analyze and understand the adoption of gamified business applications. To test this model, we developed a study using a sample of 183 bank customers, and we found that gamification significantly improved the customer's sense of social interaction, which, in turn, strongly influenced the customer's intention to use the applications. We argue that this intention to use could provide a strong benefit to the business, in term of increased customer engagement. This paper presents a new conceptual model to predict behavioral intention in regards to gamification in e-banking, illustrating seven variables that affect the adoption of e-banking by bank customers. Our findings contribute overall to a better understanding of gamification in e-banking (with the extension of Technology Acceptance Model theories, and the new variable gamification), providing important practical implications for software development and marketing practices.